Labour Studies, the Liberal Arts, and the Sociological Imagination - Wells, Richard (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
In the US, the value of liberal arts is in question as neo-liberal reformers push for a more instrumentalist form of higher education. Older traditions of worker education, however, along with more recent university-based labour studies programs, offer a compelling counter-narrative concerning the social and political purpose of higher education. Taking its cue from C.W. Mills’ notion of the sociological imagination, labour studies has the potential not only to re-energize the transformational mission of popular worker education, but reclaim the idea of higher education as a public good.